An examination of the interrelationships among NASA-TLX dimensions utilizing the DEMATEL method - Şeniz Harputlu Aksu; Aylin Adem; Erman Çakıt; Metin Dağdeviren; Waldemar Karwowski (PLoS ONE, 2025)
The NASA TLX is a survey-based method widely used to evaluate cognitive workload across six specific dimensions related to an employee’s tasks. While academic research recognizes that these dimensions may have unequal contributions to mental workload, they are often weighted using multi-criteria decision-making techniques. However, prior studies have not investigated possible relationships between the dimensions. The main objective of this paper is to explore the interconnections and dependencies among these dimensions. This study distinguishes itself by employing the Decision-Making Trial and Evaluation Laboratory (DEMATEL) technique to clarify these relationships and dependencies, and to examine how interactions between dimensions shift under different threshold conditions. The research includes three distinct impact diagrams tailored for individuals performing tasks with varying levels of cognitive workload. By considering the interdependencies among the NASA TLX dimensions, this study offers a significant advancement in the field, as these interrelationships could greatly influence the derived weights. This theoretical contribution has the potential to be groundbreaking in the realm of survey-based mental workload assessment techniques, such as the NASA TLX.